Comercio internacional entre ecuador y américa latina: un estudio empírico a partir de la aplicación de un modelo gravitacional, periodo 2000-2019. - Jonatan Neptali, Quillay Guaraca (2021)
ABSTRACT The purpose of this research is to determine what factors justify the trade flow between Ecuador and Latin America, taking into account the theory that addresses from the classical and neoclassical approach to the new theory of trade, therefore, to answer the question of this In the study, a database of the trade flow of Ecuador and 17 Latin American countries was created with a time window of 19 years, these factors were analyzed by applying a gravitational model of international trade, later four models were run in which All the independent variables were included except for the border variable, since this variable tends to explain the geographic factor with similarities to the distance variable, and this could generate multicollinearity problems, models A and B are based on ordinary least squares, and models C and D are estimated using generalized least squares (EGLS), the latter is adequately adjusted to the theoretical and methodological requirements included and reviewed in the research, noting that, the geographical distance, the GDP per capita of Ecuador and the selected countries of Latin America, the cultural aspects such as sharing a colonizer and the same language and free trade agreements are factors that influence the commercial flow of Ecuador. Key Words: Exports, trade flow, imports, gravity model, GDP. Reviewed by: MsC. Adriana Cundar Ruano, PhD. ENGLISH PROFESSOR c.c 1709268534